2020
DOI: 10.7717/peerj.8714
|View full text |Cite
|
Sign up to set email alerts
|

Heeding the psychological concerns of young cancer survivors: a single-arm feasibility trial of CBT and a cognitive behavioral conceptualization of distress

Abstract: Background.A subgroup of adolescent and young adult (AYA) survivors of cancer during adolescence report high levels of psychological distress. To date, evidence-based psychological interventions tailored to the cancer-related concerns experienced by this population are lacking. The present study aimed to (1) examine the feasibility and preliminary efficacy of an individualized cognitive behavioral therapy (CBT) intervention for AYA survivors of cancer during adolescence; and (2) identify and conceptualize canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 120 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…However, in today's digitally interconnected society, we did not anticipate that this requirement would preclude many AYAs from participating. Despite these limitations, our study participation rate remained quite high and was higher than those commonly noted in other behavioral trials [12,14]. Finally, we excluded non-English-speaking participants as the study measures and program were targeted towards an English-speaking audience.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, in today's digitally interconnected society, we did not anticipate that this requirement would preclude many AYAs from participating. Despite these limitations, our study participation rate remained quite high and was higher than those commonly noted in other behavioral trials [12,14]. Finally, we excluded non-English-speaking participants as the study measures and program were targeted towards an English-speaking audience.…”
Section: Discussionmentioning
confidence: 88%
“…Other psychosocial programs targeting AYAs have been individually delivered, did not include mind-body skill acquisition, or focused on teaching a single skill (ie, mindfulness, positive psychology) for stress reduction [12][13][14][15][16][17]25,26]. Few have targeted a wide range of AYAs, particularly during the early posttreatment period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger studies are needed to generate more conclusive data. Yet, there is growing evidence about the recruitment challenges faced by researchers testing online mental health interventions [ 31 , 109 , 110 , 111 , 112 ], with one study recruiting only 10 AYA cancer survivors out of 213 potential eligible participants contacted (4.7%) [ 113 ]. Reviews have highlighted that randomized psychosocial studies average lower opt-in rates in pediatric psycho-oncology (45.5%) relative to studies examining health behaviors (78.2%) or neurocognitive functioning (91%); group-based interventions also tend to yield lower opt-in rates [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
“… 29 e-MH interventions may help overcome practical barriers associated with accessing traditional face-to-face psychological support (eg, geographical, financial and time-related barriers) 30 that have been observed within the AYACCS population. 31 Furthermore, e-MH is associated with anonymity and privacy 32 thus potentially overcoming barriers associated with public stigma. Indeed, research has identified that the provision of e-MH interventions may be a potential solution for the AYACCS population.…”
Section: Introductionmentioning
confidence: 99%